Factors Influenced by Instructional Leadership A Literature Review - Ellza Wijaya Tanjung; Hasan Hariri; Sowiyah Sowiyah (Universitas Muhammadiyah Enrekang, 2024)
Instructional leadership is a leadership style that focuses on managing and improving the learning process in an educational environment. Several variables can be influenced by instructional leadership in schools. This article investigates the factors that can be influenced by principals' instructional leadership. This research uses the literature review method, where data is collected through articles from 2019 to 2024. There are 10 articles as references from Google Scholar. This article identifies factors such as effective schools, student academic achievement, academic culture, student and teacher achievement motivation and teacher commitment that are influenced by instructional leadership. This article can be useful from a theoretical perspective, that is, to increase knowledge about the factors that instructional leadership influences. Then, this article can be used as a reference for future research.